Crystal structure of sitagliptin dihydrogen phosphate monohydrate, C16H16F6N5O(H2PO4)(H2O). Issue 4 (11th November 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of sitagliptin dihydrogen phosphate monohydrate (sometimes referred to as sitagliptin phosphate monohydrate) has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Sitagliptin dihydrogen phosphate monohydrate crystallizes in space group P 21 21 21 (#19) with a = 6.137 108(12), b = 9.304 018(14), c = 38.307 67(10) Å, V = 2187.359(8) Å 3, and Z = 4. The sitagliptin cation folds so that the two planar portions are roughly parallel. The ammonium group of the sitagliptin cation, the phosphate anion, and the water molecule form a network of strong hydrogen bonds. The result is a two-dimensional network, parallel to the ab plane . Halfway between these hydrogen bond planes, there are planes of high fluorine density. The powder pattern is included in the Powder Diffraction File™ as entry 00-064-1500.